Puffing/micro-explosion in rapeseed oil/water droplets: The effects of coal micro-particles in water - Antonov D. V. Dmitry Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Fedorenko R. M. Roman Mikhaylovich; Nissar Z. Zuhaib; Sazhin S. S. Sergey Stepanovich (2021, 2021)
Title screen